GABALA MOUNDS IN THE CONTEXT OF RELATIONSHIPS THE EARLY BRONZE ERA IN THE CAUCASUS - Museibli, Nadzaf Alesker oglu; Agalarzade, Anar Mirsamid oglu; Ahundova, Gul'nara Kamal kyzy (History, Archeology and Ethnography of the Caucasus, 2023)
One of the main problems of investigating the Kura-Araxes cultural and historical community is to identify its local variants in the South Caucasus. At the same time, the interaction of the bearers of this community with the population of other regions also influenced the formation of these local variants. From this viewpoint, the results of investigations of the monuments in Gabala district, located in the northern region of Azerbaijan, are interesting. Archaeological monuments belonging to different periods have been discovered in the territory of the district. A certain group is made up of kurgans dating to the Early Bronze Age. In the structure of the excavated kurgans and burial rites, depending on the chronological stage, various and common features were revealed. In the village of Amili of the Gabala district, three Early Bronze Age kurgans were studied. The complex structure of these kurgans draws attention. At the same time, a dolmen-shaped megalithic structure discovered in one of them attracts attention with its uniqueness. It is interestingly, the large stones with which this structure was built are made in the form of anthropomorphic idols. Lines of various sizes were carved on them. The crescent-shaped structures built in kurgans are also of interest. The group of ceramics has the property of “making hands stained” if you touch it, hands get stained. Such pottery is not typical for the Kura-Araxes community. The structure of the kurgans and the technological indicators of ceramics show that in the 4th-3rd millennia BC there were close ties between the northern regions of Azerbaijan and the North Caucasus.
Keywords: Early Bronze Age; Kura-Araxes culture; kurgans; megalithic structure; anthropomorphic idols; burial rite; ceramics